2007
DOI: 10.1097/01.brs.0000261627.04944.cf
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Esophagus Retraction on Early Dysphagia After Anterior Cervical Surgery

Abstract: A correlation between intraoperative pharynx/esophagus retraction and postoperative swallowing disturbances could not be confirmed. The cause of the prevalence of the female gender is unknown. However, the absence of impaired deglutition in the control group suggests that a local phenomenon must be causative of swallowing disturbances following anterior cervical discectomy and fusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
57
0
3

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(63 citation statements)
references
References 27 publications
3
57
0
3
Order By: Relevance
“…2,4,7,[12][13][14]18,19,23,24,29,35,[41][42][43][44]46,47 Prospective analyses featuring questionnaires report a higher rate of dysphagia, ranging from 20% to 71%. 5,15,[25][26][27][28][30][31][32]34,35,37,38,48,49 These prospective studies are comparable to the present study. Using a questionnaire, Lee et al 27 reported the incidence of subjective dysphagia at multiple time points during the 2 years after surgery.…”
Section: Discussionsupporting
confidence: 80%
“…2,4,7,[12][13][14]18,19,23,24,29,35,[41][42][43][44]46,47 Prospective analyses featuring questionnaires report a higher rate of dysphagia, ranging from 20% to 71%. 5,15,[25][26][27][28][30][31][32]34,35,37,38,48,49 These prospective studies are comparable to the present study. Using a questionnaire, Lee et al 27 reported the incidence of subjective dysphagia at multiple time points during the 2 years after surgery.…”
Section: Discussionsupporting
confidence: 80%
“…2,5,6,9,10,12,16,18,21,22,[27][28][29]31,32 However, the associations are not consistent among studies.…”
mentioning
confidence: 79%
“…5,6,9,23 However, there are a number of studies that have reported significantly higher incidences of dysphagia in women. 2,13,21 The potential relationship between patient sex and postsurgical dysphagia remains to be clarified. Also consistent with previous reports, 2,6,13,21,23 no significant association between age and dysphagia was found in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Contributing factors include prevertebral soft tissue swelling, vocal cord paresis, 4,6,7 scar tissue formation, hardware complication and cervical graft material. 1,4,8 Risk factors that have been identified include multilevel fusion and female gender, 3,4,9,10 revision surgery, 5 and plate prominence. 2,11 Given that dysphagia is a common complication of anterior cervical spine surgery, numerous techniques have been investigated to decrease its incidence, decreased plate prominence and cuff pressure are just a few.…”
Section: Introduction Rationalementioning
confidence: 99%